Utilization of evidence-based tools and medical education literature by Canadian postgraduate program directors in the teaching and assessment of the CanMEDS roles - Asif Doja (Canadian Medical Education Journal, 2020)
Background: Researchers have shown that clinical educators feel insufficiently informed about how to teach and assess the CanMEDS roles. Thus, our objective was to examine the extent to which program directors utilize evidence-based tools and the medical education literature in teaching and assessing the CanMEDS roles.